2017
DOI: 10.1186/s12861-017-0150-4
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of Pluripotency: in vitro adaptations of a continuum of in vivo states

Abstract: Pluripotency defines the propensity of a cell to differentiate into, and generate, all somatic, as well as germ cells. The epiblast of the early mammalian embryo is the founder population of all germ layer derivatives and thus represents the bona fide in vivo pluripotent cell population. The so-called pluripotent state spans several days of development and is lost during gastrulation as epiblast cells make fate decisions towards a mesoderm, endoderm or ectoderm identity. It is now widely recognized that the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
147
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 210 publications
3
147
0
1
Order By: Relevance
“…At the opposite extreme, primed hPSCs are associated with the expression of lineage specific fate determinants that limit the range of cell types into which they can differentiate (Weinberger et al, 2016;Morgani et al, 2017). Indeed, we found that naïve hPSCs were unable to directly form forebrain organoids, consistent with recent studies showing that these cells must first pass through formative/intermediate states in order to undergo lineage-specific differentiation ( Figure S1 and Rostovskaya et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At the opposite extreme, primed hPSCs are associated with the expression of lineage specific fate determinants that limit the range of cell types into which they can differentiate (Weinberger et al, 2016;Morgani et al, 2017). Indeed, we found that naïve hPSCs were unable to directly form forebrain organoids, consistent with recent studies showing that these cells must first pass through formative/intermediate states in order to undergo lineage-specific differentiation ( Figure S1 and Rostovskaya et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, cell lineages that are established early in embryonic development, such as germline stem cells, are more effectively produced when starting from the formative intermediate state rather than the primed state. Interestingly, key transcription factors expressed during the formative state including OTX2, OCT6, SOX2, and SOX3, are also highly expressed in the early neuroectoderm (Morgani et al, 2017;Smith, 2017), thus suggesting a predisposition for these cells to form neuroectoderm. Perhaps not surprisingly, the cells in the formative state might be prone to neuroectodermal lineage commitment in the absence of BMP/ TGFβ signaling, consistent with the neural default model (De Robertis and Sasai, 1996;Munoz-Sanjuan and Brivanlou, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…hematopoietic determination. This study describes a broad resetting of NANOG-occupied genomic regions in the transition from ES cells to EpiLCs, resembling the developmental progress from the naïve inner cell mass of the blastocyst to the primed epiblast at gastrulation(Hayashi et al, 2011;Morgani et al, 2017). This study describes a broad resetting of NANOG-occupied genomic regions in the transition from ES cells to EpiLCs, resembling the developmental progress from the naïve inner cell mass of the blastocyst to the primed epiblast at gastrulation(Hayashi et al, 2011;Morgani et al, 2017).…”
mentioning
confidence: 87%
“…To investigate this possibility, we analyzed published ChIP-seq data for NANOG binding in ES and EpiLCs, which correspond to the E6.0 epiblast in the mouse embryo (Murakami et al, 2016). This study describes a broad resetting of NANOG-occupied genomic regions in the transition from ES cells to EpiLCs, resembling the developmental progress from the naïve inner cell mass of the blastocyst to the primed epiblast at gastrulation (Hayashi et al, 2011;Morgani et al, 2017). We examined a number of genomic loci, detecting binding at the Nanog locus itself in both ES cells and EpiLCs ( Fig EV4A) and in Cdx2 only in ES cells ( Fig EV4B).…”
Section: Esc-derived Embryoid Bodiesmentioning
confidence: 99%
“…To simplify mESC maintenance we tested protocols that replace the need for serum by a combination of two kinase inhibitors, specifically MEK inhibitor PD0325901 and GSK3 inhibitor CHIR99021 (2i) (Ying et al, 2008) and/or growth factors (BMP4) (Ying et al, 2003) and combined this with a suspension culture approach (Andang et al, 2008). ESCs cultured in serum-free 2i/LIF medium have homogeneous expression of pluripotency factors and lower lineage-associated gene expression compared to serum/LIF conditions (Marks et al, 2012;Morgani et al, 2017;Wray et al, 2010). Markedly, 2i/LIF cells appear similar to in vivo E4.5 epiblast cells on the transcriptome level (Boroviak et al, 2014).…”
Section: Introductionmentioning
confidence: 99%